Routledge handbook of law and society in Latin America - Sieder, Rachel; Ansolabehere, Karina; Alfonso Sierra, Tatiana (Routledge handbooks., 2019)
An understanding of law and its efficacy in Latin America demands concepts distinct from the hegemonic notions of "rule of law" which have dominated debates on law, politics and society, and that recognize the diversity of situations and contexts characterizing the region. The Routledge Handbook of Law and Society in Latin America presents cutting-edge analysis of the central theoretical and applied areas of enquiry in socio-legal studies in the region by leading figures in the study of law and society from Latin America, North America and Europe. Contributors argue that scholarship about Latin America has made vital contributions to longstanding and emerging theoretical and methodological debates on the relationship between law and society. Key topics examined include: The gap between law-on-the-books and law in action The implications of legal pluralism and legal globalization The legacies of experiences of transitional justice Emerging forms of socio-legal and political mobilization Debates concerning the relationship between the legal and the illegal. The Routledge Handbook of Law and Society in Latin America sets out new research agendas for cross-disciplinary socio-legal studies and will be of interest to those studying law, sociology of law, comparative Latin American politics, legal anthropology and development studies.